A qualitative study of green practices adoption for restaurants in Malaysia. Issue 8 (10th December 2018) - Tan, Booi Chen; Lau, Teck Chai; Yong, Gun Fie; Khan, Nasreen; Nguyen, Thi Phuong Lan
Abstract : Purpose: The purpose of this paper is to understand restaurant operators' perception towards key areas of green practices that could be adopted in the future operations of the restaurant business in Malaysia. Design/methodology/approach: The paper used a qualitative approach through face-to-face interviews. Five restaurant operators who operated their independently owned casual upscale restaurants in the Klang Valley were selected as the respondents for the interviews. Findings: Eight areas of green practices adapted from Hu et al. (2010) have been commented and proposed to be served as a guideline to design the Environmental Management System (EMS) for restaurants to go green in Malaysia. Although the feedback given on the feasibility of implementing these green practices provided by the restaurant operators were generally positive, challenges lies ahead in getting them to adopt these green practices. It required understanding of the difficulties and motivations of implementing these practices. Practical implications: An in-depth understanding from the voices of restaurant operators was essential for further policy formulation and implementation in fostering the green practices which in turn can serve as a "win-win" situation for all parties. Originality/value: There seems to be a dearth of studies conducted on the perceptions of restaurant operators about the feasibility of green practices adoption in the operation of the restaurants in Malaysia. The implementation of EMS or the adoption of green practices was a vital missing-link among the restaurants. The outcome of this paper was expected to provide new ideas and knowledge on the areas of green practices to be adopted as the environmental guidelines to operate restaurants in Malaysia.